Assessing socioeconomic vulnerability and COVID-19 infection risk among NCD patients in rural Sierra Leone: a cross-sectional study - Foday Boima; Marta Patiño Rodriguez; Stefanie A. Joseph; Mohamed S. Kamara; Alfred Gborie; Lebbie Williams; Daniel Lavalie; Chiyembekezo Kachimanga; Thierry Binde; Jean Gregory Jerome; Dale A. Barnhart; the Cross-Site (Springer, 2023)
Abstract Background In Sierra Leone, non-communicable diseases (NCDs) are an increasingly important source of mortality and morbidity. However, Sierra Leonean NCD patients' experience of direct exposure to COVID-19-related risks and indirect effects of the COVID-19 pandemic on socioeconomic determinants of health has not been described. Methods We conducted a cross-sectional telephone survey among adult (≥ 18 years) hypertensive, diabetic, and heart failure patients receiving treatment at the NCD clinic at Koidu Government Hospital (KGH) in rural Sierra Leone. We described patient demographics, COVID-19 related knowledge, and practice of infection prevention measures. Patients were categorized into nationally representative wealth quintiles using an asset-based wealth index and measures of social vulnerability were reported by clinical program and wealth category. Result Of the 400 respondents, 80.5% were between 40 and 69 years old and 46.1% were male. The majority of patients (> 90%) knew utilizing masks, social distancing, isolation from positive cases, and avoiding hand shaking were effective COVID-19 prevention measures. However, only 27.3% of the population had access to adequate handwashing facilities, 25.5% had attended crowded events in the past two weeks, and only 5.8% always used face masks. Compared with the national distribution of wealth, 33.0% of our population belonged in the richest quintile, 34.8% in the second-richest quintile, and 32.2% in the bottom 3 poorest-middle quintiles. Socioeconomic vulnerability was high overall with significant disparities between wealth categories. In the 30 days before the interview, almost 60% of the poorest-middle categories experienced one barrier to essential health services, 87.4% used at least one emergency coping mechanism to cover food, housing, or health care, and 98.4% were worried about having food. In the richest category, the proportion of patients experiencing these challenges was 32.3%, 39.5% and 81.6%, respectively. Conclusion Our patients had good knowledge of COVID-19 prevention measures; however, we found substantial discrepancies between patients' self-reported knowledge and practices. Although our population was wealthier than the national average, the NCD patients were still exposed to unacceptable levels of socioeconomic vulnerability, reflecting a high absolute poverty in Sierra Leone. Furthermore, wealth-based disparities in access to essential resources persist among NCD patients.